2002
DOI: 10.1016/s0167-2738(02)00024-3
|View full text |Cite
|
Sign up to set email alerts
|

Polymer electrolytes based on modified natural rubber

Abstract: Modified natural rubber polymer hosts having low transition glass temperatures have been investigated for use in polymer electrolytes. Two types of modified natural rubber, namely 25% epoxidised natural rubber (ENR-25) and 50% epoxidised natural rubber (ENR-50) were employed in conjunction with poly(ethylene oxide), PEO. Results are reported for ionic conductivity and thermal properties for both unplasticized and plasticized polymer electrolyte systems with lithium triflate. The samples were in the form of fre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
20
0

Year Published

2008
2008
2016
2016

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 84 publications
(20 citation statements)
references
References 14 publications
(2 reference statements)
0
20
0
Order By: Relevance
“…However, one of the biggest drawbacks in development of SPE is having low conductivity at ambient temperature [4,6]. Numerous efforts and approaches have been employed such as addition of nano-size ceramic filler/ additives, plasticizer (EC and PC), radiation, binary blending of polymers and etc [7][8][9][10][11][12].…”
Section: Introductionmentioning
confidence: 99%
“…However, one of the biggest drawbacks in development of SPE is having low conductivity at ambient temperature [4,6]. Numerous efforts and approaches have been employed such as addition of nano-size ceramic filler/ additives, plasticizer (EC and PC), radiation, binary blending of polymers and etc [7][8][9][10][11][12].…”
Section: Introductionmentioning
confidence: 99%
“…In order to prevent the decrease in physical and mechanical properties the composite polymer electrolytes (CPEs) was prepared by adding inorganic filler into SPEs or GPEs. According to the previous studies [7], they also reported that the introduction of inorganic filler into the SPE system will increase the mechanical stability of the samples as well as improve the physical contact between electrode/electrolyte interfaces. Therefore, in the present investigation methyl grafted natural rubber (MG30) was doped with LiTf to prepare a SPE and we choose silicon dioxide (SiO2) nanosize powder as inorganic filler and dimethylene carbonate (DMC) as a plasticizer to be added into SPE in order to optimize the physical properties of the SPE and hence ionic conductivity.…”
Section: Introductionmentioning
confidence: 94%
“…Recently, modified natural rubber such as epoxidized natural rubber (ENR) and poly(methyl methacrylate)-grafted natural rubber (PMMA-g-NR) based SPE drew the attention of many researchers [5][6][7][8] due to the attractive attributes such as low glass transition temperature (T g ), soft elastomer characteristic at room temperature and good elasticity. Besides that, modified NR gives excellent contact between an electrolytic layer and an electrode in a battery system.…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, these composites remain in the plastic crystal states with clear solid-solid phase transitions and appear as an icy solid, even when LiODFB doping level increased up to 30%. It is known that adding an appropriate proportion of plasticizer can enhance ion mobility, hence increasing the ion conductivity of the electrolyte (Osman et al, 2001;Glasse et al, 2002). Therefore, IPC5 doped with 10% PC (commonly used plasticizer in gel polymer electrolytes) was prepared to further improve the ion conductivity.…”
Section: Dsc and Ionic Conductivitymentioning
confidence: 99%